A new species of Phaenostoma d’Orchymont, 1937 (Coleoptera: Hydrophilidae) from Brazil - Clarkson, Bruno; Takiya, Daniela Maeda (Zootaxa, 2017)
A new species of Phaenostoma d’Orchymont, 1937 (Hydrophilidae: Sphaeridiinae: Coelostomatini) from Brazil is des-cribed and illustrated. Phaenostoma tupiniquim sp. nov. is described based on an adult male specimen from the Caatinga biome in Ceará State (Northeastern Brazil) and two specimens from uncertain localities, but most likely Mato Grosso and Pará States (Central-western and Northern Brazil, respectively). An updated key to the five known species is provided.